Formalin Removal from Archival Tissue by Critical Point Drying - Sheng-Guo Fang; Qiu-Hong Wan; Noboru Fujihara (BioTechniques, 2002)
The extraction of high-quality nucleic acid may be problematic in formalin-fixed tissues because of cross-linking between proteins and DNA. Old fixed tissue specimens do produce fragmented DNA (<1.2 kb), which is only used for PCR amplification. Here we show that high molecular weight DNA (>194 kb) can be successfully extracted from fixed tissue samples (16–70 years old) by gradual dehydration and critical point drying. The reliability of extracted DNA was measured by its ability to serve as a template for the amplification of mtDNA fragments (403 and 1198 bp) and an nDNA fragment (1844 bp). In addition, fingerprinting analysis was performed using DNA from fixed human tissue to ensure the ability of extracted DNA to hybridize with the DNA probe. DNA derived by this method can be subject to amplification, complete digestion by restriction endonuclease, and hybridization.